RELOKASI PASAR DOCK KE PASAR KELAKAP TUJUH OLEH PEMERINTAH KOTA DUMAI - Mazzalul Ma’rufy; Zaili Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT Dumai city government continues to make improvements in the city of Dumai. Among them is relocating the market on Jalan M.H Thamrin. The traders rejected the government's decision due to many factors. The background of this research problem is to find out what causes traders who sell around Jalan M.H Thamrin not to move to a market that has been created by the government, namely the Kelakap Tujuh market. This study examines Dumai City Government Development Communication in Public Spatial Arrangement Post Relocation of Dumai Dock Market. This study aims to determine how the relocation of the Dock Market to the Pasar Kelakap Tujuh by the Dumai City Government. Analysis The data used in this study is data using qualitative methods by collecting data with the method of observation (Observation), and interviews, while the sources of this study amounted to 4 people consisting of 1 Head of Market Services Department of Trade Dumai City and 3 traders . The results showed that the Dumai City Government through the Trade Service had carried out good communication where starting from the beginning of the construction of the seven catfish market which became the location for the transfer of the Dumai Dock market until the inauguration of the seven catfish market, the government always involved the community and traders in every process of developing this seven catfish market starting from from negotiations with related parties. Keywords: Individual, Organizational Scope Factor